Elizabeth Anscombe on Just War, Legitimate Killing, and Double Effect - DENG, Yunyan (Public Realm. Postgraduate and Early Career Journal of Political Philosophy, 2025)
This paper examines Elizabeth Anscombe’s theory of just war and argues that Anscombe’s central thesis is that nothing can justify the deliberate killing of the innocent in war. This paper covers two aspects. First, by discussing the justification and limitations of legitimate killing, Anscombe claims that civilians, as the innocent, can never be the target of legitimate killing. Second, Anscombe’s distinction between intention, foreseeing, and accident in her action theory explains how the principle of double effect has been misused to justify the killing of civilians in war; and her analysis of “intention” responds to the challenge of “how do we know people’s intention?” and explains the applicability of the principle of double effect in the context of killing civilians in war.